Corrosion behavior of Zinc or 55%Al-Zn hot-dip coated steel in 0.5 m NaCl solution - Granada, Maite (2015)
A comparative study on the anticorrosive behaviour of 55%Aluminum-Zinc- alloy and Zinc hot-dip coated carbon steel immersed in 0.5 mol/L NaCl solution was performed using DC (polarization curves) and AC (electrochemical impedance spectroscopy) techniques. Also, the corrosion products formed under these testing conditions were characterized using XRD, SEM and EDS. The experimental results showed that the corrosion resistance of the 55%Al-Zn alloy coating showed a synergistic effect being more satisfactory than the each metal used separately and the Zn tested coating. This was attributed to the effectiveness of two forms of protection: the cathodic protection and the barrier effect (afforded by a basic zinc- aluminumcarbonate layer) acting together. The morphological characteristics of their corrosion products also differed.